Additive-free cobalt-catalysed hydrogenation of carbonates to methanol and alcohols. Issue 13 (18th June 2019) - Ferretti, Francesco; Scharnagl, Florian Korbinian; Dall'Anese, Anna; Jackstell, Ralf; Dastgir, Sarim; Beller, Matthias
Abstract : Homogeneously cobalt-catalyzed hydrogenation of cyclic and acyclic carbonates: beneficial effects of 2, 2, 2-trifluoroethanol and triphos-derivatives. Abstract : Reduction of various organic carbonates to methanol and alcohols can be achieved in the presence of a molecularly-defined homogeneous cobalt catalyst. Specifically, the use of Co(BF4 )2 in combination with either commercial or tailor-made tridentate phosphine ligands allows for additive-free hydrogenations of carbonates. Optimal results are obtained at relatively mild conditions (120 °C, 50 bar hydrogen pressure) in the presence of xylyl-TriphosL4 .